Comparison of fiscal system progressivity over time: Theory and application in Mexico - Huesca Reynoso, Luis; Araar, Abdelkrim (Estudios Económicos de El Colegio de México, 2016)
Assessing the progressivity of a fiscal system is relevant to develop a global idea on the extent of redistribution. We analyze the evolution of how fiscal policy affects the design of a fiscal system, as well as its progressivity over time. We assess the dynamics of progressivity during the period 2002-2012. This work adopts a non-parametric approach to measure the progressivity of taxes and transfers in Mexico, using a common support of comparison. Progressivity increased and high levels of polarization and inequality generate a non-negligible impact on its level when the common support of comparison is applied.